Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support, September 20-21, 2019, in Vienna, Austria (2019)
This book contains the proceedings of the 7th International Conference on Sport Sciences Research and Technology Support (icSPORTS 2019), which is taking place in Vienna, Austria from 20 to 21 September 2019. icSPORTS is co-organized by Technische Universität Wien. icSPORTS 2019 is sponsored by the Institute for Systems and Technologies of Information, Control and Communication (INSTICC) and held in cooperation with European College of Sports and Exercise Physicians (ECOSEP), European Association for Sport Management (EASM), the European Federation of Sport Psychology (FEPSAC), European Society of Biomechanics (ESB), International Association of Computer Science in Sport (IACSS), Grupo de Interesse em Fisioterapia do Desporto (GIFD), International Association of Sport Kinetics (IASK), Portuguese Society of Physical Education (SPEF), Portuguese Sports Federation for Persons with Disabilities (FPDD), European College of Sport Science (ECSS), Societa` Italiana di Anatomia e Istologia (SIAI), Sport Sciences Research Institute of Iran, European Society of Movement Analysis for Adults and Children (ESMAC) and The International Sport and Culture Association (ISCA). The Conference Technical Program includes oral presentations and poster presentations, organized in four simultaneous tracks: Computer Systems in Sports, Health and Support Technology, Signal Processing in Human Movement and Sport Performance and Support Technology. All full papers as well as all short papers are included in this book of proceedings. The conference also includes a thematic session on Kinesiology in Sport and Medicine: from Biomechanics to Sociodynamics, chaired by Igor Gruic of the Faculty of Kinesiology, University of Zagreb, Croatia. A major aspect of the program is the inclusion of three plenary keynote lectures held by internationally renowned researchers, namely: Bill Baltzopoulos (Liverpool John Moores University, United Kingdom), Erich Müller (University of Salzburg, Austria) and Bjørn H. Olstad, (Norwegian School of Sport Sciences, Norway). icSPORTS received 43 submissions from all continents, of which 28% are presented as full papers. To evaluate each submission, a blinded review was performed by the Program Committee, whose members are highly qualified researchers in icSPORTS topic areas. All papers presented at this conference will be available at the SCITEPRESS Digital Library (http://www.scitepress.org). We would like to express our thanks to all participants. First of all, to the authors whose quality work is the essence of this conference. Secondly, to all members of the Program Committee and Auxiliary Reviewers who helped us with their expertise. We would also like to thank the invited speakers for accepting our invitation to share their expert knowledge and vision. Finally, a word of appreciation for the hard work of the secretariat: organizing a conference of this level is a task that can only be achieved by the collaborative effort of a dedicated and highly capable team. We wish you all an inspiring conference and an unforgettable stay in the lovely region of Vienna, Austria. We hope to meet you again next year for icSPORTS 2020, details of which soon will be available at http://www.icsports.org.